Predicting factor of online purchasing behaviour among university students in UiTMCT / Mohd Fadzlee Mazlan - Mazlan, Mohd Fadzlee (2022)
As e-commerce grows rapidly, online shopping or purchasing is now not solely gaining its reputation across the world but becoming a common purchasing method. Survey Consist of 588 was contributed among university student an UiTMCT. Online purchasing increase rapidly but there have several people not fully utilize online purchasing platform. The problem is people not fully utilize online purchasing which it is now become one of common platform in daily activity especially for university student. The perceived factor of online shopping has emerged as a critical circumstance in this investigation since it has a direct impact on people’’s online purchasing behaviour. The aim of this project is to identify the factor that influence the online purchasing behaviour among university student, to build prediction model for factor that lead online purchasing behaviour and to demonstrate the applicability of the prediction model using a dashboard researcher use methodology that suitable for the project which is CRISP-DM methodology. The correlation analysis, clustering analysis and Random Tree algorithm were selected for this project for the result of the correlation analysis, there have a relationship between factor score and online purchasing behaviour. Several prediction rules already been produced with high interestingness by using K-Mean clustering algorithm and Random Tree algorithm. The final result was represented in dashboard. The result of the analysis had met the objective of this project.